The book of Chatbots : from Eliza to ChatGPT - Ciesla, Robert (Springer, 2024)
Primitive software chatbots emerged in the 1960s, evolving swiftly through the decades and becoming able to provide engaging human-to-computer interactions sometime in the 1990s. Today, conversational technology is ubiquitous in many homes. Paired with web-searching abilities and neural networking, modern chatbots are capable of many tasks and are a major driving force behind machine learning and the quest for strong artificial intelligence, also known as artificial general intelligence (AGI).Sophisticated artificial intelligence is changing the online world as advanced software chatbots can provide customer service, research duties, and assist in healthcare. Modern chatbots have indeed numerous applications - including those of a malicious nature. They can write our essays, conduct autonomous scams, and potentially influence politics. The book of Chatbots is both a retrospective and a review of current artificial intelligence-driven conversational solutions. It explores their appeal to businesses and individuals as well greater social aspects, including the impact on academia. The book explains al relevant concepts for readers with no previous knowledge in these topics. Unearthing the secrets of virtual assistants such as the (in) famous ChatGPT and many other exciting technologies, The book of Chatbots is meant for anyone interested in the topic, laypeople and IT-enthusiasts alike